POVERTY LEVEL TRENDS BASED ON THE PREVALENCE OF INSUFFICIENT FOOD CONSUMPTION AND ITS IMPACT ON ECONOMIC GROWTH IN WEST SUMATRA: A SUSTAINABLE DEVELOPMENT GOALS (SDGS) PERSPECTIVE - Eliza, Eliza; B, Syamsul Amar; Riani, Novya Zulva; Dewi, Muharika; Yenni, Zefri (Universitas Padjadjaran, 2025)
This study aims to analyze poverty trends based on the prevalence of food insufficiency and its impact on economic growth in West Sumatra Province from the perspective of the Sustainable Development Goals (SDGs). Using a quantitative approach and Pearson correlation analysis method, this study evaluates secondary data from 2019 to 2024 obtained from the Central Statistics Agency (BPS). Economic growth is measured by the average Gross Regional Domestic Product (GDP) as an indicator of economic inclusion. The analysis results show a negative correlation between poverty levels and economic growth, with coefficient values ranging from -0.197 to -0.378, but not statistically significant (p > 0.05). The low determination value (R² between 3.8% and 14.3%) indicates a limited contribution of food poverty to GRDP variations. Although GRDP tends to increase annually, the prevalence of food insufficiency also shows an increase, with a peak in 2023. These findings indicate that economic growth in West Sumatra is not fully inclusive and has not succeeded in reaching poor communities effectively. The implications of this research emphasize the importance of integrating statistical indicators of food security and poverty in SDGs-based regional development planning, in order to realize more just, sustainable, and equitable growth.